An ultrastructural comparison of the attachment sites between Gregarina steini and Cryptosporidium muris - Valigurová, Andrea; Hofmannová, Lada; Koudela, Bretislav; Vávra, Jirí (The Journal of eukaryotic microbiology, 2007)
Early developmental stages of Gregarina steini Berndt, 1902 from the intestine of Tenebrio molitor larvae were studied by transmission electron microscopy. The formation and structure of the eugregarine attachment site were compared with comparable features found on the feeder organelle of Cryptosporidium muris Tyzzer, 1907, from the stomach of experimentally infected rodents. The similarity of the attachment strategy between both organisms was revealed. The membrane fusion site in G. steini, formed by the trophozoite plasma membrane, host cell plasma membrane and a membrane-like structure limiting the cortical zone of the epimerite, resembles the Y-shaped membrane junction between the host cell plasma membrane, the trophozoite plasma membrane and membrane surrounding the anterior vacuole in C. muris. The anterior vacuole of C. muris appears to be the precursor of the feeder organelle and its structure is very similar to the epimeritic bud and the cortical zone of G. steini trophozoites. In both investigated organisms, the apical complex disappears early during cell invasion. The possibility of the epicellular location of Cryptosporidium on the surface of host cells is discussed.
Keywords: Tenebrio; Cryptosporidiosis; kryptosporidióza; střeva; larva; Intestines; Apicomplexa; Stomach; Female; Host-Parasite Interactions; krysa rodu Rattus; Cell Adhesion; Cryptosporidium; zvířata; trofozoiti; přežvýkavci; ženské pohlaví; žaludek; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Rats; Larva; Animals; buněčná adheze; Ruminants; interakce hostitele a parazita; Trophozoites